2016
DOI: 10.2147/ijn.s103760
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection effects of undoped and silver-doped ceria powders of nanometer crystallite size

Abstract: Being endowed with an ability of capturing and releasing oxygen, the ceria surface conventionally assumes the role of catalyzing redox reactions in chemistry. This catalytic effect also makes possible its cytotoxicity toward microorganisms at room temperature. To study this cytotoxicity, we synthesized the doped and undoped ceria particles of 8–9 nm in size using an inexpensive precipitation method and evaluated their disinfecting aptitudes with the turbidimetric and plate count methods. Among the samples bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Particles were synthesized via a variation and modification of a published protocol [43]. 160mM cerium nitrate hexa-hydrate and 40mM silver nitrate (99.9%; Sigma Aldrich) solutions were prepared separately prior to combining in equal volumes to yield final concentrations of 80mM and 20mM, respectively.…”
Section: Synthesis Of Silver-doped Ceria Nanoparticles (Agcnp)mentioning
confidence: 99%
“…Particles were synthesized via a variation and modification of a published protocol [43]. 160mM cerium nitrate hexa-hydrate and 40mM silver nitrate (99.9%; Sigma Aldrich) solutions were prepared separately prior to combining in equal volumes to yield final concentrations of 80mM and 20mM, respectively.…”
Section: Synthesis Of Silver-doped Ceria Nanoparticles (Agcnp)mentioning
confidence: 99%
“…CeO 2 -NPs have also been used as fuel catalyst additives [ 20 ], in polish surface treatment, and in cosmetics and sunscreens [ 21 ]. More recently, CeO 2 -NPs have been used as therapeutic agents to prevent blindness caused by light overexposure [ 22 ], to prevent age-related macular degeneration [ 23 ], and as anti-microbial agents by disrupting bacterial electron transport chain [ 24 , 25 ] and reducing the infectivity of certain viruses in vitro [ 26 ]. Despite their excellent catalytic and multi-enzyme mimetic properties [ 27 ], the potential toxicity of CeO 2 -NPs to different organisms raises concerns [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, CeO 2 boosts the material chemical activity by allowing electron transfer from appropriate species to an oxide surface. Recent research has shown that optimal dopant element selection and incorporation quantities can further enhance capabilities resulting from surface defects . It is possible to increase the number of structural defects (oxygen vacancies) while preserving a fluorite-type crystal structure by promoting Ce 4+ reduction into Ce 3+ or by doping with transition or rare-earth elements. , The number of oxygen vacancies on the oxide surface is increased by doping silver in ceria, which can improve catalytic properties and disinfection activities, notably against drug-resistant bacteria. , It should link the synergistic effects of cerium redox with bacterial silver killing, enhancing the sterilizing effect on bacteria and benefiting community health . Transition metals and metalloids are appealing antimicrobial agents because of their ability to target bacteria, viruses, and fungi without being specific …”
Section: Introductionmentioning
confidence: 99%